Complex model for the assessment of the location of high-rise buildings in the city urban structure - Tamošaitienė, Jolanta; Šipalis, Juozapas; Banaitis, Audrius; Gaudutis, Ernestas (International Journal of Strategic Property Management, 2013)
As the economic conditions in Eastern European countries were changing, so were changing the visions of urban development, which came to be associated with private property and a pursuit of business investments. One of the most important tasks in urban planning today remains efficient models to find a place for high-rise buildings in the urban pattern. The paper aims to identify the most efficient ways to locate high-rise buildings in Vilnius, in reference to many years of related experience of other European cities. Article presents a multi-stage complex assessment model for the location of high-rise buildings in the urban structure. The proposed model is composed from three decision making methods. The first method applied in our research was the SWOT analysis (Strengths, Weaknesses, Opportunities and Threats), which allows assessing current European practices with different models for the location of high-rise buildings in the urban pattern. To determine the weights of criteria reflecting social-economic, political and aesthetic urban planning aspects, the method of expert judgement was used. The next method used was SAW (Simple Additive Weighting), which makes it possible to rank the best alternatives of high-rise buildings location using a pre-selected set of criteria. The research proves that SWOT, expert judgment and SAW are appropriate methods for various kinds of urban planning tasks.First Publish Online: 3 Apr 2013